The negative effects of food price inflation on pupils’ attainment and performance at school in Algeria - AMRANI, Abdelmadjid (Dirassat Journal Economic Issue, 2017)
This study attempts to assess the impact of food price inflation on the loss of human capital mainly through school wastage in Algeria. The results obtained by means of both a theoretical investigation, and by means of a field work conducted in many parts of the country clearly indicate: For a significant percentage of families, more than half of the overall income is spent on food products. Food price inflation engenders on behalf of poor families considerable cuts on educational spending which negatively affect learners’ school performance. In the context of lack of financial support, vulnerable families have serious difficulty in keeping their children at school, and learners encounter severe handicaps in their learning acquisition process and school attainment. These very facts in turn induce high school wastage and high inefficiency of the public sector performance. The solution to such a problem requires (i) a better understanding of both parents and learners’ difficulty, and (ii) the definition of a sound scheme of material, financial help, and moral support in favor of vulnerable families and pupils.